To 200 years of Independence in Peru and the role of History counted from the otredad - Huanca-Arohuanca, Jesús Wiliam (2022)
The idea of Republic has collapsed when scholars in history opted for partiality by only highlighting the role of the main characters, leaving aside the true protagonists of history. The construct unfolds within the qualitative design, accompanied by the grounded theory in which the ontology and the suigéneris version of the four “others” that pose their position on the role of history are collected. The intention of the treaty is not to detract from the contribution of the men who daily strived to keep the science called history on its feet, but to critically question its role, by not showing or presenting the events experienced from otherness. So, if today this subject is changing, there are still certain shortcomings of continuing to write from the glass desk and comfort without sociohistorical criteria; for, if it continues like this, history as such is condemned to nothing more than a past of bad breath.